PATTERNS IN WOUND HEALING PROCESS AFTER BRANCIAL CLEFT CYST EXCISION IN CHILDREN - P.I. Tkachenko; S.A. Belokon; N.M. Lokhmatova; O.B. Dolenko; Yu.V. Popelo; N.M. Korotych (Український стоматологічний альманах)
The course of the wound healing process after surgical intervention on brancial cleft cyst excision should be considered as a stereotyped inflammatory-reparative reaction of the body, characterized by staged aseptic inflammation, regeneration and fibrosis. Clinically and even morphologically, it is difficult to determine the stages of the wound healing process in the temporal aspect, since they are consistent and interconnected.